Levofloxacin Determination in Pharmaceutical Tablets by Sensitive Spectrofluorometric Method with L-Tryptophan as a Fluorescent Probe - Abdullah, Kurdo A.; Qader, Aryan F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Proper dosage, therapeutic effectiveness, patient safety, and quality control throughout manufacture and storage can only be achieved by closely monitoring the concentration of pharmaceutical products. Aprecise and reliable spectrofluorometric approach for quantitative analysis and detection of levofloxacin (LEVO) in various pharmaceutical products was developed in this work using the fluorescent reagent L-tryptophan. When L-tryptophan, which has its inherent fluorescence signal quenched by LEVO, is mixed with Britton-Robinson buffer solution (pH 9.0), a stable ion-associated complex forms. The fluorescence intensity of L-tryptophan decreased at 365 nm after excitation at 281 nm. The method showed linearity for LEVO concentrations from 0.3 to 18.0 μg/mL, with a minimum detectable value of 0.10 μg/mL. An effective linear relationship (R2 = 0.9985) between the concentration and fluorescence intensity (ΔF) was obtained. This technique has been well-proven to be minimally affected by impurities commonly found in pharmaceutical formulations. The results were validated through comparative analyses with high-performance liquid chromatography. The study revealed that both equivalence levels and analytical quality (as measured by precision and accuracy) are very satisfactory. This study addresses the increasing demand for established and reliable methods in the quality control of pharmaceutical products.